Prospects for the Incorporation of the Digital Ruble into Russia’s Monetary Turnover: Attributes and Principles for Developing a Trusted Digital Environment - M. A. Abramova; N. N. Kunitsyna; E. I. Dyudikova (Финансы: теория и практика)
The rapid nature of the modernization of monetary turnover, accompanied by geopolitical risks against the background of post-pandemic economic recovery and the regionalization process, no longer just arouses the discursive interest of society, but becomes an indispensable condition of the new reality. The process of money turnover transformation by introducing digital currencies into circulation in the wave of digitalization among world powers lagging behind the evolving environment of the cryptocurrency industry is developing into a process of formalization of metaverses and penetrates deeper into the socio-economic reality. The problem of the Russian practice of developing the payment environment consists in its catching-up character, caused by the spontaneous formation of the digital society, resulting in the expansion of the scope of alternative finance outside the legal field. The purpose of the paper is to determine the inherent attributes of the digital trusted environment necessary to ensure digital ruble turnover, based on an empirical study of society’s perceptions about the prospects for using the digital form of the national monetary unit by representatives of various generations. We used systematization, grouping, comparative and content analysis, surveys, and the quota method to achieve the paper’s purpose. The survey involved 35,327 residents from different regions. As a result, the authors revealed the low level of readiness of society for the introduction of the digital ruble as a substitute for cash and cryptocurrency. The paper focuses on the need for an integrated approach to the disclosure of the digital ruble’s value and benefits, which contributes to its successful launch and promotion in the market. The results of the research highlight the importance of correspondence in the digital ruble category “digital currencies”, and also the impossibility of making incorrect decisions in the transformation of money turnover, which leads to the growth of risks of digital inequality, the clash of interests of certain groups of the population in the prevailing behavioral patterns in the form of a cautious attitude to digital finance with insufficient financial literacy.